Multiple Primary Tumours, How Frequent we can Offer Curative Therapy? - Elemam, Omima; Abdelkhalek, Seham; Abdelmoety, Doaa; Baraka, Reem; Yousef, Mervat (Asian Pacific Journal of Cancer Care, 2020)
Background: Patients with Multiple-primary Malignancies are usually excluded from clinical trials. Clinical information re-distribution, associations, response to treatment and prognosis are scared. Collecting information will help us to expect the impact of prior therapies and to teach us how to best treat them. This study aims to report cases in our society and to see if we have a special predilection of certain Multiple-primary Malignancies in our region based on different geographic and environmental risk factors. Our retrospective study aims to collect these cases and follow their prognosis and treatment response as well as looking for any relation to cancer therapy. Methods: A retrospective study included patients who have two or more histologically diverse primary malignancy, either as synchronous or metachronous malignancy. The study was conducted in King Abdullah Medical City, Saudi Arabia over 7 years period from 2012 to 2019. We collected all patient’s clinicopathological information, treatment, and modalities. Results: We collected 53 cases of multiple primary malignancies 26were synchronous (48%) and 27 were metachronous (52%). Out of 53 patients, 29 (60 %) were females and 14 (40 %) were males. The most common sites for synchronous are breast and endometrial cancer. Curative treatment could be offered in 19 patients (73%). For metachronous tumours, the most common primary tumour was breast cancer, while the most common second malignancy was colorectal cancer. Curative treatment could be offered in 15 patients (53%). Conclusion: Multiple primary malignancies represent a small proportion of our cases, with no special predilection in our society. Multiple primary malignancies did not signify a poor prognosis; besides nonmetastatic cases showed a good response to therapy. We should not forget the possibility of a second primary tumour as these cases can be reasonably treated with curative intent.